2016
DOI: 10.1177/1933719115616496
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Receptivity Markers in Mice Stimulated With Raloxifene Versus Clomiphene Citrate and Natural Cycles

Abstract: Ovulation induction therapy with clomiphene citrate can suppress endometrial receptivity. Raloxifene may be an alternative therapeutic for women with ovulatory disorders. This study aimed to compare the expression of endometrial receptivity markers, including homeobox gene 10 (HOXA10), integrin β3, and leukemia inhibitory factor (LIF), as well as pinopode production during the implantation window in mice stimulated with raloxifene and clomiphene citrate and natural cycles. Thirty-six 8-week-old female Kunming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
20
0
3
Order By: Relevance
“…The effect of miR‐26a on the surface morphology of EECs were detected by SEM (Chen et al, ). In short, glutaraldehyde‐fixed (2.5%) cell samples were thoroughly washed with PBS buffer, dehydrated in a graded ethanol series, placed in 2% isoamyl alcohol for 3 hr, and received critical point drying.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of miR‐26a on the surface morphology of EECs were detected by SEM (Chen et al, ). In short, glutaraldehyde‐fixed (2.5%) cell samples were thoroughly washed with PBS buffer, dehydrated in a graded ethanol series, placed in 2% isoamyl alcohol for 3 hr, and received critical point drying.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced endometrial thickness is caused by CC-induced inhibition of epithelial cell proliferation and oestrogen response element transactivation in the endometrium (Amita et al , 2010). Furthermore, ovarian stimulation using CC adversely affects uterine receptivity by reducing the endometrial expression of Homeobox gene 10, integrin αvβ3 and leukaemia inhibitory factor during the implantation period (Bao et al , 2009; Chen et al , 2016). A recent systematic review (Gadalla et al , 2018) reported the adverse effects of CC administration on the endometrium, which resulted in lower pregnancy and LBR.…”
Section: Discussionmentioning
confidence: 99%
“…Объем регрессирующих пиноподий (поздняя лютеиновая фаза) начинает снижаться, на поверхности появляются складки из цитоплазматической мембраны и вновь становятся заметными микроворсинки [17,54,55]. Различают несколько степеней относительного количества пиноподий в зависимости от доли трансформированных секреторных клеток в образце: «0» -полное отсутствие; «1» -незначительное количество (пиноподии покрывают менее 25% площади поверхности); «2» -умеренное количество (пиноподии занимают 25-50% площади поверхности); «3» -множество (более 50% площади поверхности образца занято пиноподиями) [56].…”
Section: электронная микроскопияunclassified